2020
DOI: 10.1186/s12885-020-06921-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic model based on the geriatric nutritional risk index and sarcopenia in patients with diffuse large B-cell lymphoma

Abstract: Background: Systemic inflammation and cachexia are associated with adverse clinical outcomes in diffuse large Bcell lymphoma (DLBCL). The Geriatric Nutritional Risk Index (GNRI) is one of the main parameters used to assess these conditions, but its efficacy in DLBCL is inconclusive. Methods: We retrospectively reviewed 228 DLBCL patients who were treated with R-CHOP immunochemotherapy (rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone). The patients were stratified according to GNRI sco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 41 publications
0
21
1
Order By: Relevance
“…The major limitation of this study is its retrospective nature ( 22 ), which may introduce inherent selection bias by recruiting DLBCL patients who were diagnosed and followed at tertiary medical centers. To minimize the inherent biases of the retrospective study and ensure the homogeneity of treatment, we included only patients with de novo DLBCL treated with R-CHOP and excluded patients with primary central nervous system and mediastinal lymphoma, immunodeficiency-associated tumors, transformed non-Hodgkin lymphoma and posttransplant lymphoproliferative disorder, which might result in a selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…The major limitation of this study is its retrospective nature ( 22 ), which may introduce inherent selection bias by recruiting DLBCL patients who were diagnosed and followed at tertiary medical centers. To minimize the inherent biases of the retrospective study and ensure the homogeneity of treatment, we included only patients with de novo DLBCL treated with R-CHOP and excluded patients with primary central nervous system and mediastinal lymphoma, immunodeficiency-associated tumors, transformed non-Hodgkin lymphoma and posttransplant lymphoproliferative disorder, which might result in a selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…Although patients' comorbidities have been shown to increase the risk of morbidity and mortality in patients receiving cancer therapy [33], the mechanisms by which hypoalbuminemia affects clinical outcomes remains unclear. Hypoalbuminemia may relate to nutritional status or disease biology as albumin is a prognostic factor for survival in DLBCL and is affected by proinflammatory mediators including interleukein-6, interleukin-1, and tumor necrosis factor [20,22,31,[34][35][36]. Future work should investigate the potential mechanisms underlying this relationship to identify novel biomarkers to identify those at the highest risk for treatment toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies showed that the Charlson Comorbidity Index (CCI), a standardized scoring system to predict mortality with respect to the weight of comorbidities, can predict the clinical outcome in lymphoma patients [ 14 , 15 ]. Parameters of the nutritional status, including the serum albumin level, body weight, and body mass index (BMI), were also explored as predictors [ 11 , 12 , 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Previous studies revealed that skeletal muscle and fat mass wasting identified by computed tomography (CT) are valuable for predicting the clinical outcomes in DLBCL patients [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the GNRI to be a better prognostic factor than the serum albumin level, body weight, or BMI alone in hematologic malignancies [ 29 , 30 , 31 ]. Regarding lymphoma, the GNRI was associated with long-term survival in DLBCL patients [ 13 , 16 , 17 , 18 ]. However, the impact of the GNRI on different treatment strategies has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%